INCIDENCE, MORTALITY AND PREVALENCE AS INDICATORS OF TUBERCULOSIS BURDEN IN WHO REGIONS, COUNTRIES OF THE WORLD AND THE RUSSIAN FEDERATION. PART 1. TUBERCULOSIS INCIDENCE AND PREVALENCE - I. A. Vаsilyevа; E. M. Belilovsky; S. E. Borisov; S. A. Sterlikov (Туберкулез и болезни лёгких)
The article  presents  data on two of the main epidemiological  rates defining the burden  of tuberculosis  in the system of WHO global statistics tuberculosis  incidence and mortality.The article specifies the formation of WHO assessment of tuberculosis incidence and provides main data on the evaluation  and notification  of new cases in certain countries,  WHO regions and worldwide.Data presented in the article include the comparison of definitions of incidence and values of registered incidence of tuberculosis, obtained in Russia, worldwide and countries of WHO European Region.The article speculates on the tuberculosis detection in WHO understanding, in particular on the use of systematic screening. The explanation is given why the rate of prevalence is not commonly used in the latest WHO publications.